Developing PISA-like Mathematics Tasks in Musi Rawas Regency Contexts using Lesson Study - Fauziah, Anna; Pandra, Viktor (Mathematics Education Journal, 2023)
This study aims to produce valid and practical PISA-like mathematics tasks which potentially have an effect on students' problem-solving ability in the contexts of Lake Aur and pindang Musi Rawas dish. This study used the design research method consisting of preliminary and formative evaluation stages. In addition, the PISA-like mathematics tasks were also developed based on lesson study. The research subjects were ninth graders of SMPIT Annida Lubuklinggau. Data were collected using walkthrough, documentation, observation, and questionnaire techniques and analyzed qualitatively. This research produced a sharing task in the context of Lake Aur and a jumping task in the context of pindang Musi Rawas dish which were valid, practical, and potentially influential to students' mathematical ability in identifying and solving PISA-like mathematics tasks. The results show that the use of context and collaborative learning in solving PISA-like mathematics tasks made it easier for students to understand the questions and made the learning process more enjoyable. This was because the contexts of Lake Aur and pindang Musi Rawas dish were known and familiar to students in their daily lives and because the learning process involved students teaching each other.